Kasaysayang Buhay, Kabayanihan at Lipunan: Ang Talambuhay ni Tandang Sora sa Pagtuturo ng Kasaysayan - Reguindin-Estella, Janet (Review of Women's Studies, 2023)
One gap that remains to be thoroughly addressed in the teaching and study of Philippine history is the relatively limited, if not absence of, space allotted to the discussion of the role and issues of women. In most textbooks, what receives much emphasis is the heroism displayed by men while there are only brief mentions about that of women. This, in turn, can result in the students’ lack of knowledge and understanding of women’s role and importance in our history and society. We can therefore say that to an extent, women continue to be "silenced" in most narratives of Philippine history. With this reality, the significant role of the teacher in situating women in the teaching of history becomes more apparent. This paper attempts to present various strategies on how to include the biography of Melchora Aquino or Tandang Sora (1812–1919) in teaching history, and in the process, show the heroic example of a woman amidst a social crisis. This study also aims to reiterate that heroism knows no gender and that women greatly contributed to the nation’s struggle for freedom.